2022
DOI: 10.1038/s41598-022-05720-y
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous polyserine and polyleucine are toxic to recipient cells

Abstract: Repeat-associated non-AUG (RAN) translation of mRNAs/transcripts responsible for polyglutamine (polyQ) diseases may generate peptides containing different mono amino acid tracts such as polyserine (polyS) and polyleucine (polyL). The propagation of aggregated polyQ from one cell to another is also an intriguing feature of polyQ proteins. However, whether the RAN translation-related polyS and polyL have the ability to propagate remains unclear, and if they do, whether the exogenous polyS and polyL exert toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Aggregated misfolded proteins such as HTT have the general ability to propagate between cells 23 . In line with this phenomenon, we reported that aggregated 13A, 13S and 13L entered PC12 cells and some of them changed their morphology 22 , 24 . Especially, microglial cells are expected to facilitate such propagation because microglial cells phagocytose cell debris and damaged neurons 25 .…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…Aggregated misfolded proteins such as HTT have the general ability to propagate between cells 23 . In line with this phenomenon, we reported that aggregated 13A, 13S and 13L entered PC12 cells and some of them changed their morphology 22 , 24 . Especially, microglial cells are expected to facilitate such propagation because microglial cells phagocytose cell debris and damaged neurons 25 .…”
Section: Introductionsupporting
confidence: 70%
“…1 c) inside the cells (Fig. 1 ) as seen in PC12 cells 22 , 24 . Ortho images of the XZ-axis cross section view verified that the 13A (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations